Spatiotemporal distribution and determinants of overweight or obesity among urban women in Ethiopia: a multivariate decomposition analysis - Melkalem Mamuye Azanaw; Edgeit Abebe Zewde; Alemayehu Digssie Gebremariam; Fentaw Teshome Dagnaw; Dessalegn Tesfa Asnakew; Ermias Sisay Chanie; Dejen Getaneh Feleke; Sofonyas Abebaw Tiruneh (BMC, 2022)
Abstract Background Overweight /obesity is a global public health concern. It is higher among women than men in most continents of the world. This study aimed to determine the spatiotemporal distribution and determinants of changes in overweight/obesity over time among urban women in Ethiopia. Methods We used data from three consecutive Demographic and Health Surveys in Ethiopia (2005, 2011, and 2016). The total weighted sample of 1112 in 2005, 3569 in 2011, and 3071 in 2016 urban women were included in the analysis. The primary outcome measure of this study was the spatiotemporal distribution and trends over time in overweight/obesity. Factors contributing to change in overweight/obesity were examined using a logit-based multivariate decomposition analysis. Results Overweight/obesity increased from 14.2% in 2005 to 21% in 2016. Approximately 61.3% of the overall increase in overweight/obesity among urban women was due to the difference in coefficient (difference in the effect of characteristics) across the surveys. Changes in the composition of women aged 25-49 years (β = 0.012, 95% CI 0.008, 0.015), married women (β = 0.010, 95% CI 0.006, 0.014), women with formal education (primary: β = 0.007, 95% CI 0.003, 0.011, higher education: β = 0.014, 95% CI 0.006, 0.022), women with formal employment (β = 0.006, 95% CI 0.001, 0.011), and women with informal employment (β = − 0.002, 95% CI − 0.003, − 0.0004) were factors contributing to the change in overweight/obesity from 2005 to 2016. The risk difference (RD) in women's overweight/obesity significantly varied across regions in urban Ethiopia. Furthermore, a high proportion of overweight/obesity was found mainly in Tigray, Oromia, Amhara, and Addis Ababa. Conclusions The rate of overweight/obesity among women in urban Ethiopia has shown a significant increase over the last 11 years. This rate change was due to changes in the composition of women's age, educational status, marital status, and employment status. Therefore, program interventions should be targeted at older (> 25 years), educated, married, Addis Ababa residents, and formally employed women.